Combination Therapy for Bacterial Pathogens: Naturally Derived Antimicrobial Drugs Combined with Ulva lactuca Extract - Bamunuarachchi, Nilushi I.; Khan, Fazlurrahman; Kim, Young-Mog (Infectious Disorders - Drug Targets, 2022)
Background: With the growing incidence of microbial pathogenesis, several alternative strategies have been developed. The number of treatments using naturally (e.g., plants, algae, fungi, bacteria, and animals) derived compounds has increased. Importantly, marine-derived products have become a promising and effective approach to combat the antibiotic resistance properties developed by bacterial pathogens. Furthermore, augmenting the sub-inhibitory concentration of the naturally-derived antimicrobial compounds (e.g., hydroxycinnamic acids, terpenes, marine-derived polysaccharides, phenolic compounds) into the naturally derived extracts as a combination therapy to treat the bacterial infection has not been well studied. Objective: The present study was aimed to prepare green algae Ulva lactuca extract and evaluate its antibacterial activity towards Gram-positive and Gram-negative human pathogenic bacteria. Also, revitalize the antibacterial efficiency of the naturally-derived antimicrobial drugs and conventional antibiotics by mixing their sub-MIC to the U. lactuca extracts. Methods: Extraction was done using a different organic solvent, and its antibacterial activity was tested towards Gram-positive and Gram-negative pathogens. The minimum inhibitory concentration (MIC) of U. lactuca extracts has been determined towards pathogenic bacteria using the micro broth dilution method. The viable cell counting method was used to determine the minimum bactericidal concentration (MBC). The fractional inhibitory concentration (FIC) assay was utilized to examine the combinatorial impact of sub-MIC of two antibacterial drugs using the micro broth dilution method. The chemical components of the extract were analyzed by GC-MS analysis. Results: Among all the extracts, n-hexane extract was found to show effective antibacterial activity towards tested pathogens with the lowest MIC and MBC value. Furthermore, the n-hexane extracts have also been used to enhance the efficacy of the naturally-derived (derived from plants and marine organisms) compounds and conventional antibiotics at their sub-inhibitory concentrations. Most of the tested antibiotics and natural drugs at their sub-MIC were found to exhibit synergistic and additive antibacterial activity towards the tested bacterial pathogens. Conclusions: The combining of U. lactuca n-hexane extracts with natural drugs resulted in synergistic and additive bactericidal effects on Gram-positive and Gram-negative human pathogenic bacteria. The present study shows a new alternative strategy to revitalize the antimicrobial activity of naturally derived compounds for treating human bacterial pathogens.
Keywords: natural drugs